Tahap Penggunaan Projektor Overhead di Sekolah-Sekolah Luar Bandar: Satu Tinjauan - Ab Shukor, Mohd Jan (1998)
'This surveys aims to gather information on; (1) the standards of existing equipment overhead projectors used in rural secondary schools. (2) how much and how often the overhead projectors are being used. (3) was there encouragment in using the overhead projectors. (4) are teachers being exposed to the right techniques/courses in using overhead equipment in teaching. (5) how much awareness do teachers have regarding the advantages ill using overhead projectors in teaching and learning.